Navigating the Hybrid Workforce: Challenges and Strategies in Modern HR Management - Bryan Givan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study explores the complexities surrounding the management of a hybrid workforce in contemporary organizations, with a specific focus on PT. Darmasindo Intikaret. The research investigates the relationships between workforce productivity, employee satisfaction, organizational adaptation, and the adoption of hybrid work arrangements. Through a comprehensive analysis utilizing path analysis techniques, the study reveals significant direct and indirect effects among these variables. Findings highlight the pivotal role of organizational adaptability as a mediator, facilitating the successful implementation of hybrid work practices. The research underscores the importance of fostering organizational adaptability and prioritizing initiatives to enhance workforce productivity and employee satisfaction to navigate the challenges and opportunities presented by the hybrid workforce paradigm effectively. By embracing these insights, organizations can position themselves for success in an increasingly dynamic and evolving work environment.